Sexual Harassment in Female Students at Tribhuvan University: A Narrative Inquiry Research (Quest Journal of Management and Social Sciences, 2023)
Background: Higher education establishments in Nepal also disclose information on sexual harassment incidents. Sexual harassment is a detrimental encroachment onto the educational domain that extends beyond scholarly discussions. It is an undesirable, offensive, and frequently menacing behaviour that jeopardises a student's well-being.Objectives: This study examines the experiences of female students at Tribhuvan University regarding sexual harassment in the classroom. It aims to assess the prevalence of sexual harassment and identify its various forms among female students.Methods: Adopting a qualitative narrative inquiry research design, we included teachers and students from the Central Department of Education, with information collected from selected female students until data saturation was reached. In-depth interviews were used as the primary data collection method, and both primary and secondary sources were qualitatively and descriptively analysed.Results: The findings reveal a disturbing reality where female students at Tribhuvan University faced sexual harassment from their classmates, teachers, and university staff. The study identifies three primary forms of sexual harassment: verbal, physical, and cyber sexual harassment. Cybersexual harassment emerges as the most prevalent form, significantly impacting the physical and mental well-being of the affected students.Conclusion: Sexual harassment occurs in Nepalese higher education institutions, although it is less common among female students who are able to voice their concerns in an articulate and natural way. Those who feel intimidated struggle to voice their opinions or live in fear of facing a higher risk. The detrimental effect of this type of sexual harassment on the personality development of female students is emphasised.Keywords: Girl student, Sexual harassment, Tribhuvan University, Forms of sexual harassment